Potential Markets for Florida Ginger - Kevin Athearn; Jonathan Adam Watson; Paul Fisher; Maria Paz Kinslow; Marina Burani-Arouca; Brian Pearson; Celina Gómez (EDIS)
This publication explores the potential markets for ginger (Zingiber officinale) grown in Florida, focusing on opportunities in fresh produce, food and beverage ingredients, and nursery markets. Ginger is widely used in a variety of culinary dishes and wellness products, primarily consumed as the rhizome, or ginger root. The US fresh produce market for ginger is dominated by imports from China, Peru, and Brazil, making price competition challenging. Florida ginger producers face significant competition, but by focusing on quality, differentiation, and exploring niche markets, they can enhance profitability.